Neuroprotective effect of melatonin on soluble Aβ1–42-induced cortical neurodegeneration via Reelin–Dab1 signaling pathway. (3rd July 2017) - Hu, Chunli; Wang, Pan; Zhang, Shuman; Ren, Lili; Lv, Yiheng; Yin, Rui; Bi, Jing
Abstract: Objective: Soluble Aβ1–42 oligomers play a vital role in the development and pathogenesis of Alzheimer's disease (AD). Melatonin could delay the progress of AD through multiple mechanisms. Reelin–Dab1 signaling plays an important role in AD, including neuronal function and synaptic plasticity. However, whether melatonin could exert its neuroprotective function against soluble Aβ1–42 -induced neurotoxicity during AD development through regulating Reelin–Dab1 signaling remains poorly understood. Methods: AD rat model was established by soluble Aβ1–42 repeated intracerebroventricular injection. Using immunohistochemistry and Western blot analyses, the effect of melatonin on synaptic plasticity, neuritic degeneration, and astrocyte activation was investigated in cerebral cortex. Meanwhile, the expression of Reelin and Dab1 was also examined in cerebral cortex. In our in vitro study, Reelin–Dab1 signaling was inhibited by Reelin antibody, and neuroprotective effect of melatonin against Aβ1–42 was further determined. Results: Melatonin ameliorated the neurotoxiciy and astrocyte activation induced by Aβ1–42 in the cerebral cortex. Melatonin also blocked the reduction in Reelin and Dab1 expression induced by Aβ1–42 . Using in vitro study, Reelin inactivation completely abolished the protective effect of melatonin against Aβ1–42 -induced neurotoxicity. Discussion: Melatonin might play its neuroprotective role against Aβ1–42 through mediating Reelin–Dab1 signaling pathway. Melatonin could be a safe and remarkable therapeutic candidate for AD and other aged-associated neurodegenerative diseases.